2012
DOI: 10.1371/journal.pone.0046631
|View full text |Cite
|
Sign up to set email alerts
|

Iron Regulator Hepcidin Exhibits Antiviral Activity against Hepatitis C Virus

Abstract: Hepatitis C viral infection affects 170 million people worldwide. It causes serious chronic liver diseases. HCV infection has been implicated in iron accumulation in the liver and iron overload has been shown to be a potential cofactor for HCV associated hepatocellular carcinoma progression. The underlying mechanisms are not understood. Human hepcidin, a 25 amino acid peptide mainly produced by hepatocytes, is a key regulator of iron metabolism. Alteration of hepcidin expression levels has been reported in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 48 publications
4
37
1
Order By: Relevance
“…This interval coincides with the substantial decrease in ferritin following infection and could signify a viral need for iron. Although past research showed that hepcidin suppressed HCV replication, acting as an antiviral agent, 26 our data remain in agreement with researchers who suggested a positive regulatory role for hepcidin on HCV replication. 3,11 Macrophages induce hepcidin transcription in Huh7 cells, 22 while macrophagic hepcidin may regulate iron uptake and release in an autocrine manner.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This interval coincides with the substantial decrease in ferritin following infection and could signify a viral need for iron. Although past research showed that hepcidin suppressed HCV replication, acting as an antiviral agent, 26 our data remain in agreement with researchers who suggested a positive regulatory role for hepcidin on HCV replication. 3,11 Macrophages induce hepcidin transcription in Huh7 cells, 22 while macrophagic hepcidin may regulate iron uptake and release in an autocrine manner.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, upon established infection, hepcidin expression dropped in our in vitro model and in patient sera, 12,13 in step with studies from chronic HCV patients with low intrahepatic HAMP mRNA 24 and decreased serum hepcidin, 12,13 and earlier in vitro RNA data. 25,26 Secreted protein expression was also increased throughout infection, albeit not as dramatically as mRNA. The latter may be due to post-transcriptional regulation of HAMP gene expression, including mRNA destabilisation 27 and secretion modulation.…”
Section: Discussionmentioning
confidence: 97%
“…21,22 On the contrary a direct antiviral activity of hepcidin against HCV replication in cell culture was also proved. 23 Foka et al attempt to clarify these mutual interactions between HCV, hepcidin and iron. Their results bring new light on the impact of hepcidin and iron on the promotion of HCV infection in its early phase.…”
mentioning
confidence: 99%
“…The inhibitory effect appears to occur at the viral replication level. Taken together, these results suggest that both exogenous addition of hepcidin peptide and over-expression of hepcidin could attenuate HCV replication in cell models (29) . It is possible to develop a therapy using hepcidin.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Liu et al (29) further examined the anti-HCV activity of hepcidin by gene over-expression and knockdown. The data clearly show that over-expression of hepcidin reduced HCV expression, while knockdown of hepcidin induced viral RNA expression.…”
Section: Discussionmentioning
confidence: 99%